Analisis Pengaruh Media Sosial X Terhadap Sikap dan Perilaku Remaja Menggunakan K-Means Clustering - Raihan, Farid; Sutisna (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research aims to analyze the influence of social media X on adolescent attitudes and behavior using the K-means clustering method. Social media has an important role in everyday life, especially among teenagers, who are vulnerable to external influences in shaping their attitudes and behavior. In this study, data was collected through a survey covering aspects such as frequency of use, type of content consumed, and social interactions on the platform. The K-means clustering method is used to group teenagers based on their patterns of social media use and the characteristics of their attitudes and behavior. The results of the analysis show that there are several clusters that indicate a significant relationship between the intensity of use of social media X and changes in teenagers' attitudes and behavior. These findings provide valuable insights for parents, educators, and policy makers in understanding the impact of social media on adolescent development and formulating strategies to mitigate its negative effects.